The National Development Act 1979 : a critical analysis : a thesis presented in partial fulfilment of the degree of Master of Arts in Sociology at Massey University - Boyle, Andrew Dorrington (Massey University, 1986)
This thesis analyses the National Development Act 1979. The theories of Claus Offe and Jurgen Habermas are used to analyse the Act as a capitalist state planning process. Two major theoretical distinctions provide a framework for the thesis. These are: (1) the distinction between technical rationalisation and practical rationalisation and (2) the contradiction between accumulation and legitimation. A clarification is made in the concept of legitimation to distinguish between actual or deserved legitimation and nominal or unfounded legitimation. An analysis of legislation, Tribunal reports, Cabinet papers and other documents shows the Act to be a dual planning process: one process occurring in secret and relating to accumulation; the other in public and relating to legitimation. Thus the Act is analysed as a technical planning process through which the state attempts to reconcile accumulation and legitimation.
Keywords: New Zealand National Development Act 1979; Regional planning